PENGUATAN RANTAI PASOK UMKM MELALUI MANAJEMEN PERSEDIAAN DAN DISTRIBUSI YANG EFISIEN - Bahdin Nur Tanjung; Jumadiah Wardati; Gita Nainggolan (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service Program (PKM) activity aims to strengthen the MSME supply chain through the implementation of efficient inventory and distribution management. The main problems faced by partners include inaccurate stock, frequent stockouts/overstocks, the absence of a reorder point, untidy inventory recording, and unmeasured distribution costs. The program is implemented through supply chain process assessments, training and workshops on inventory recording, establishing stock policies (minimum-maximum/ROP), improving simple warehouse layouts and flows, distribution planning (routes, schedules, delivery consolidation), and assistance in implementing tools (stock cards/Excel/Google Sheet). The outputs include inventory and distribution SOPs, recording templates, indicator dashboards, and implementation trials on participating MSMEs. The targeted results are increased stock accuracy, reduced stockouts, and distribution cost efficiency.